Evaluasi Sistem Oracle Fusion Human Capital Management Pada Proses Performance Appraisals di PT. XYZ - Nurwita, Siti Rakhmawati; Zarlis, Muhammad (JATISI, 2024)
The implementation of the Enterprise Resource Planning (ERP) system in the human resources scope at PT. XYZ, one of the credit companies in Jakarta, plays a role in managing the performance appraisal process. Oracle Fusion Human Capital Management system with the Talent Management module were used to support the integrated performance appraisal process. In its implementation, there were issues regarding the system's function not aligning with the expected business processes within the system. This study aims to analyze the issues and evaluate the Oracle Fusion HCM system at PT. XYZ, with the goal of providing appropriate recommendations to PT. XYZ to enhance the utilization of the Oracle Fusion HCM system in managing the current performance appraisal process. The research methods used requirement gathering, literature study, and Fit/Gap Analysis (FGA). The research results provided an evaluation and recommendation for the system function misalignment issues faced by PT. XYZ, with 70% of the requirements are Fit and 30% are Partial Fit. The recommended solution is to customize the system's functions to align with company requirements, with a degree of fit of Partial Fit.